Sustainability of Islamic Economics in The Political Domain in Mojokerto - Aji Prasetyo; Muhammad Yazid; Yulia Kurnia Firdausia (Maliki Islamic Economics Journal, 2021)
Economy and politics influence each other. A changing political map will affect policy to economic conditions and vice versa. Likewise with Islamic economics, its development was influenced by political power during the emergence of Islamic economics until today. Islamic political economy has a positive value for Indonesia in an effort to accelerate the empowerment of small and medium enterprises as an element of economic growth. One of the areas for Islamic economic instruments to become part of national policy is regulation. Through research with qualitative methods and a literature study approach, the researcher wants to analyze the regulations on the Islamic economy in Mojokerto district which has many micro, small and medium enterprises. Researchers conducted this research with the aim of analyzing the sustainability of Islamic economic values to all components of government apparatus and business actors in Mojokerto Regency and at the same time offering regulations to the Mojokerto Regency government which focuses on efforts to increase the size of the Islamic economic industry in institutional expansion. This study provides the results, first, Islamic economic values have not been sustainable in the political economy of Mojokerto Regency. Second, the sustainability of the Islamic economy in Mojokerto Regency can be realized in the political economy of government through policies or regulations that improve the Islamic financial industry by synergizing it with the community to empower MSMEs.